G72(P) Another tube in scrotum: an unusual cause of hydrocele. (25th October 2020) - Rehman, L; Kamal, M; Piracha, M; Power, B; Shahid, M
Abstract : Aim: To report a case of a child presented with unilateral scrotal pain and hydrocele. Method: 27 months old boy with known background of hydrocephalus, mild global delay and chromosomal deletions, had his VP shunt inserted 7 months ago. He presented in emergency department with one day history of vague symptoms of right scrotal pain and swelling. It was noticed by his mother while giving bath who also felt some tube like consistency in the upper part of right scrotum. Physical Examination revealed a well looking boy who wasn't in any distress/pain with a CRT<2 sec. His vitals were normal for his age. Systemic examination was unremarkable apart from mild right sided hydrocele and coiled tube in the right scrotum. He was reviewed by surgical team to R/O right sided torsion. Impression was VP tube in Right Scrotum which was confirmed by x-ray pelvis. He was transferred to tertiary care surgical team for Elective hernioplasty. Results: VP shunt tip in scrotum is among rare complication of procedure as in our case. 1 Far end of tube in peritoneum goes in and out of scrotum via patent processus vaginalis and could be felt on examination. 1 2 Conclusion: Surgical exploration and bilateral hernioplasty is mandatory to prevent testicular torsion and other potential complications. 1–3 References: Albala DM, Danaher JW, Huntsman WT. Ventriculoperitoneal shunt migration into the scrotum. Am Surg 1989 (11);55:685–688. Alonso-Vanegas M, Alvarez JL, Delgado L, Mendizabal R, Jimenez JL, Sanchez-Cabrera JM. Gastric perforation due to ventriculo-peritoneal shunt. Pediatr Neurosurg, ( 1994);21:192–194. Agarwal T, Pandev S, Niranian A, Jain V, Mishra S, Agarwal V. Unusual complication of ventriculoperitoneal shunt surgery . Pediatr Neurosci 2009(2);4:122–123.